1959
DOI: 10.1126/science.130.3373.452
|View full text |Cite
|
Sign up to set email alerts
|

10-Hydroxy-Δ 2 -Decenoic Acid, an Antibiotic Found in Royal Jelly

Abstract: 10-Hydroxy-Delta(2)-decenoic acid, the major component of the lipide fraction of royal jelly, exhibits antibiotic activity against many bacteria and fungi. This fatty acid is less than one-fourth as active as penicillin against Micrococcus pyogenes and less than one-fifth as active as chlortetracycline against Escherichia coli. It also slows the growth rate of Neurospora sitophila and some unidentified molds. The salt of this compound is considerably less active than the free acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(111 citation statements)
references
References 5 publications
2
104
1
4
Order By: Relevance
“…Blum, Novak and Taber (1959) and Krell (1996), respectively conducted studies demonstrating the inhibitory effects on fungi and the royal jelly beneficial antiviral in vitro effect. Another fact to consider is that Good Manufacturing Practices (GMP) were used for collecting the samples, no trace of plant material, fungus, bacteria, or nonhuman animal material that could pose risks contamination of the sample was found.…”
Section: Microbiological Quality Of Royal Jelly Samplesmentioning
confidence: 99%
“…Blum, Novak and Taber (1959) and Krell (1996), respectively conducted studies demonstrating the inhibitory effects on fungi and the royal jelly beneficial antiviral in vitro effect. Another fact to consider is that Good Manufacturing Practices (GMP) were used for collecting the samples, no trace of plant material, fungus, bacteria, or nonhuman animal material that could pose risks contamination of the sample was found.…”
Section: Microbiological Quality Of Royal Jelly Samplesmentioning
confidence: 99%
“…Several positive effects of RJ are reported: immune system stimulation, activation of the vegetative and central nervous systems etc. The main RJ acid 10-hydroxy-2-decenoic acid (10-HDA) is known to have a high antimicrobial effect (Blum et al, 1959;Melliou and Chinou, 2005). Research data suggest that the 10-HDA found in RJ may inhibit the vascularization of tumors (Izuta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A certain number of derivatives of the title compounds (E)-non-2-enoic acid (C9) and (E)-dec-2-enoic acid (C10) exhibit interesting properties, e.g., 10-Hydroxy-2-decenoic acid isolated from royal jelly shows good antibiotic activity against many bacteria and fungi [6,7]. 4-hydroxy-trans-2-nonenoic acid as a derivate of C9 acts as a receptor ligand in the cerebral cortex and hippocampus and elevated concentrations can be found in patients with Alzheimer's and Parkinson's disease [8].…”
mentioning
confidence: 99%